Comparison of metal ions release and corrosion potential from different bracket archwire combinations (An in vitro study) - Asmaa M Khamees; Sami K Al-Joubori (College of Dentistry/ University of Baghdad, 2014)
Background: Esthetic treatment is the options of patient seeking orthodontic treatment. Therefore this study was conducted to measure the concentration of Aluminum, Nickel, Chromium and Iron ions released from combination of monocrysralline brackets with different arch wires immersed in artificial saliva at different duration, to evaluate the corrosion point on different parts of the orthodontic appliances before and after immersion in artificial saliva, and to evaluate the corrosion potential of each group of the orthodontic appliances. Material and methods: Eighty orthodontic sets prepared. Each set represents half fixed orthodontic appliance, from the central incisor to the first molar, for the maxillary arch, each set consisted of molar band, five brackets, half arch wire and ligature elastic.These sets are divided into two groups: Group A: with monocrystalline brackets divided into five subgroups (each subgroup has ten sets), but differ in arch wires, as numbered stainless steel, nickel-titanium, thermally activated, coated stainless steel and coated nickel-titanium arch wires respectively. Group B: with stainless steel brackets divided into three subgroups (also each subgroup has ten sets), but differ in arch wires, as numberedstainless steel, nickel-titanium, and thermally activated arch wires respectively. Used optical microscope to check the corrosion points, and used potentiostat techniques to indicate corrosion rate and tendency. Results: The greatest concentration of Aluminum and nickel ions release during the 1st week in group A, then sharply decreased in the 2nd week. The release of chromium ion released increase with increase intervals, while iron ion released decrease with increase time. Both nickel and chromium ions increase with increase intervals in group B,while iron increase to the maximum at 3rd weeks, then began to degrease. Optical microscope displayed pitting, crevices, and intergranular corrosion. Potentiostat techniques indicated that increase corrosion when used stainless steel and coated nickel titanium than others arch wires with group A, while corrosion increase with nickel titanium than stainless steel arch wires with group B. Conclusions: Non-significant difference in the total nickel, chromium and iron release in group B. Aluminum and iron increase in A4 and A5, while nickel and chromium increase in A1 and A2.The total released amounts of metals ions in both groups were less than the amounts of daily intake.